A Digital Twin concept for the prescriptive maintenance of protective coating systems on wind turbine structures. Issue 3 (June 2022) - Momber, Andreas W; Möller, Torben; Langenkämper, Daniel; Nattkemper, Tim W; Brün, Daniel
The application of protective coating systems is the major measure against the corrosion of steel for tower sections of wind turbines. The inspection, condition monitoring and maintenance of protective coating system is a demanding and time-consuming procedure and requires high human effort. The paper introduces for the first time a Digital Twin concept for the condition monitoring and prescriptive maintenance planning for surface protection systems on wind turbine towers. The initial point of the concept is an in-situ Virtual Twin for the generation of reference areas for condition monitoring. The paper describes the integration of an online image annotation and processing tool, a maintenance model, corrosive resistance parameters, structural load parameters, and sensor data into the Digital Twin concept. The prospects of the concept and its practical relevance are shown for tower structures of large onshore wind turbines.